Physiological Characteristics of Type 1 Diabetes Patients during High Mountain Trekking - Bartłomiej Matejko; Andrzej Gawrecki; Marta Wróbel; Jerzy Hohendorff; Teresa Benbenek-Klupa; Dorota Zozulińska-Ziółkiewicz; Maciej T. Malecki; Tomasz Klupa (Journal of Diabetes Research)
In this study, the aim was to provide observational data from an ascent to the summit of Mount Damavand (5670 meters above sea level (m.a.s.l), Iran) by a group of people with type 1 diabetes (T1DM), with a focus on their physiological characteristics. After a 3-day expedition, 18 T1DM patients, all treated with personal insulin pumps, successfully climbed Mount Damavand. Information was collected on their physiological and dietary behaviors, as well as medical parameters, such as carbohydrate consumption, glucose patterns, insulin dosing, and the number of hypo- and hyperglycemic episodes during this time frame. The participants consumed significantly less carbohydrates on day 3 compared to day 1 (16.4 vs. 23.1 carbohydrate units; p=0.037). Despite this, a gradual rise in the mean daily glucose concentration as measured with a glucometer was observed. Interestingly, the patients did not fully respond to higher insulin delivery as there was no significant difference in mean daily insulin dose during the expedition. There were more hyperglycemic episodes (≥180 mg/dL) per patient on day 3 vs. day 1 (p<0.05) and more severe hyperglycemic episodes (>250 mg/dL) per patient on days 2 (p<0.05) and 3 (p<0.05) vs. day 1. In summary, high mountain trekking is feasible for T1DM patients with good glycemic control and no chronic complications. However, some changes in dietary preferences and an observable rise in glucose levels may occur. This requires an adequate therapeutic response.